PENGARUH BUDAYA ORGANISASI, DIKLAT DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN, KOMUNIKASI DAN PARIWISATA KABUPATEN PURWOREJO - Agus Dwi Atomoko (Politeknik Sawunggalih Aji, 2017)
The aim of this research is to examine the influence or effect of cultural of organization of education and training to the performance of staff with motivation as variable intervening of empires study at Department of Connection, Communication, Information, and Tourism of Purworjo’s District. Data were analyzed using research instrument analysis which is includes examine of validity using analysis correlation product moment, examine of reliability using Cronbach’s alpha technique, examine of hypothesis using Rule of Abralisis technique. The result of this research shows that: 1) there are positive and significant influences of cultural of organization to motivate the staff, 2) there are positive and significant influences to the education and training to motivate the staff , 3) there are positive and significant influences of cultural of organization to the performance of the staff, 4) there are positive and significant influences to the education and training to the performance of the staff, 4) there are negative motivation to the performance of the staff. The direct influence of education and training and cultural of organization the performance more dominant then undirect influence throught motivation. Key words: cultural organization, education and training, motivation.